A profile of dental assistants working in Quezon City - Sto.Tomas, Nova M.; Frange, Melanie Ruth K. (Adviser).
The dental assistant is a valuable and essential member of the dental office team. They increase the efficiency of the dentist in providing oral care, by working chairside, and saving the dentist from doing routine tasks like receiving patients and cleaning up the office. This study aims to describe the characteristics of dental assistants working in Quezon City. A survey questionnaire was distributed last December 1999 to dental assistants in Quezon City dental clinics, via convenience sampling. Answers of the 68 respondents were considered, encoded, tabulated and interpreted via the measures of central tendency, frequency distribution and percentages. Results of the survey revealed that dental assisting is a job catering to young, unmarried females in their mid-twenties. Most learn and receive their training while on the job, while those who had formal training did more comprehensive procedures. They have chairside, laboratory and clerical functions. They work full-time nine hours a day, and five days a week, receiving a monthly salary of P4,000 to P6,000. Considering that many complain of small salary, they still remain in their jobs.
Seminar Paper--Doctor of Dental Medicine--University of the Philippines Manila.
Keywords: Dental assistants